2006
DOI: 10.1002/jcp.20798
|View full text |Cite
|
Sign up to set email alerts
|

Myogenic differentiation of dermal papilla cells from bovine skin

Abstract: Cells from the dermal papilla and dermal sheath of hair follicles exhibit pronounced plasticity in vitro, being capable of adopting fat, bone, hematopoietic, and nerve cell phenotypes. In this study, we show that bovine dermal papilla cells (DPC) are also capable of undergoing skeletal muscle differentiation. DiI labeled DPC incorporated into myotubes when co-cultured with differentiating C(2)C(12) myoblasts. Bovine-specific PCR assays showed that the muscle markers MyoD and myogenin were up-regulated, confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The activation of stem cells in the bulge region is the basis of hair growth. Studies 16 , 17 have proved that HFSCs have the ability to differentiate into fat, bone, muscle, and cartilage tissues. Through in vitro and in vivo experiments, Lako et al 18 found that HFSCs have the ability to differentiate into hematopoietic cells, which can help improve the hematopoietic function of mice.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of stem cells in the bulge region is the basis of hair growth. Studies 16 , 17 have proved that HFSCs have the ability to differentiate into fat, bone, muscle, and cartilage tissues. Through in vitro and in vivo experiments, Lako et al 18 found that HFSCs have the ability to differentiate into hematopoietic cells, which can help improve the hematopoietic function of mice.…”
Section: Discussionmentioning
confidence: 99%
“…3 Further investigations showed the differentiation potential of these cells toward adipogenic, osteogenic, myogenic, and neurogenic lineages. 5,7,33 Finally, using an inductive microenvironment, Gang et al demonstrated odontogenic potential of the cultured vibrissae follicle dermal papilla cells. 6 In fact, it seems that the hair follicle dermal papilla cells are an important repository of the stem cells with a high degree of plasticity and a striking regenerative capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Given this point, it can be said that these cells are one kind of embryonic cells which have remained in the adult system. 3 Therefore, the dermal papilla cells have attracted many scientists because of their potential in the regulation of development and growth, although it is assumed that they are a source of multipotent mesenchymal cells which have a high differentiation potential 4 as they can differentiate into adipogenic, osteogenic, 5 odontogenic, 6 and myogenic lineages, 7 and also repopulate the hematopoietic system. 3 Besides, lineage analysis indicates that both hair and whisker follicle dermal papillae contain neural-crestderived cells.…”
Section: Introductionmentioning
confidence: 99%
“…DSCs may contribute to the fibroblast population of interfollicular skin and to wound healing . DPCs are able to differentiate in adipogenic, osteogenic, neural, hematopoietic, and even myogenic lineages . DPCs also regulate the balance among epithelial matrix production, progenitor proliferation, and hair production during the hair growth phase .…”
Section: Discussionmentioning
confidence: 99%